TRADISI HAROA: SARANA PENANAMAN NILAI-NILAI BUDAYA MELALUI AJARAN ISLAM MENURUT PEMIKIRAN YUSUF AL-QARADHAWI - Cornelius Kasmin (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
Haroa tradition is one of the traditions practiced by the Muna community, Southeast Sulawesi. Through this research, the author analyzes the sociological role of the haroa tradition for the heterogeneous Muna community. This research focuses on the role of the haroa ceremony in enhancing togetherness and solidarity as well as instilling cultural values that have been lived by the community. This research used qualitative methods with literature review and interview techniques. The author found that the haroa ceremony functions as a space for the community to foster togetherness and build brotherhood and unity in living together. The process of providing food, togetherness in prayer and eating together becomes a means of building closeness, kinship and brotherhood for the community. In addition, the author also found that the instillation of cultural values is also emphasized in this tradition. The scholars provide values that can be a guide for the community in living together. The use of cultural elements in instilling values in the community is in line with the thoughts of Yusuf Al- Qaradhawi. Al- Qaradhawi emphasized the importance of using cultural elements in instilling Islamic values in the community. The use of cultural elements must be maintained so as not to conflict with Islamic law.